Inelastic scattering of 72, 74Ni off a proton target. (June 2016) - Cortés, M L; Doornenbal, P; Obertelli, A; Pietralla, N; Werner, V; Authelet, G; Baba, H; Calvet, D; Château, F; Corsi, A; Delbart, A; Gheller, J-M; et al.
Abstract: Inelastic scattering of 72, 74 Ni off a proton target was performed at RIBF, RIKEN, Japan. The isotopes were produced by the fission of 238 U on a thick Beryllium target and were then selected and identified on an event-by-event basis using the BigRIPS separator. Selected isotopes were focused onto the liquid hydrogen target of the MINOS device and gamma rays from the reactions were measured with the DALI2 array. The energy of the ions in the middle of the target was 213 MeV/u. Outgoing particles were identified using the ZeroDegree spectrometer. Here, we report on the current status of the data analysis and preliminary results for the proton inelastic scattering cross sections for both isotopes.